Antibiotic related acute kidney injury in patients treated for open fractures. Issue 3 (March 2016) - Pannell, William C.; Banks, Kian; Hahn, Joseph; Inaba, Kenji; Marecek, Geoffrey S.
Abstract: Objective: Antibiotic administration during the treatment of open fractures has been shown to reduce infection rates and is considered a critical step in the management of these injuries. The purpose of this study was to determine if aminoglycoside administration during the treatment of open fractures leads to acute kidney injury. Methods: Patient records at a level I trauma centre were reviewed for adult patients who presented in 2014 with open fractures were screened for inclusion. Patients were excluded with fractures of the phalanges, metatarsals, and metacarpals, with isolated traumatic arthrotomies, or pre-existing renal dysfunction. Charts were reviewed for patient age, gender, race, past medical history, medication history, injury severity score, intravenous dye studies and fracture type. Patients were divided into those given cefazolin (Group A) and cefazolin with gentamicin (Group B). Laboratory values were used to determine which patients developed kidney dysfunction as measured using the RIFLE criteria. Wilcoxon–Mann–Whitney test and Chi-square were used to compare interval and categorical variables, respectively. Significance was set at P < 0.05. Results: One-hundred and fifty-nine patients met inclusion criteria. Forty-one (25%) patients were given cefazolin alone and 113 (68%) patients were given cefazolin with gentamicin. Ten (18%) patients with Gustilo-Anderson type III fractures were given cefazolin alone and 67 (67%) patients with types I or II fractures were given a cefazolin with gentamicin. Baseline characteristics and risk factors for renal dysfunction did not vary between groups. Two (4.8%) patients in Group A and 5 (4%) patients in Group B developed acute kidney injury ( P = 0.599). Conclusions: Gentamicin use during the treatment of open fractures does not lead to increased rates of renal dysfunction when used in patients with normal baseline renal function.